2010
DOI: 10.1111/j.1744-7348.2010.00406.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of cereal and pasture viruses in New Zealand's native grasses

Abstract: This study provides evidence for frequent and multiple invasions of New Zealand's native grasses by exotic cereal and pasture viruses. Fifteen native and three exotic grasses from 29 North Island and six South Island sites were surveyed for the presence of viruses using enzyme‐linked immunosorbent assay (ELISA). Barley yellow dwarf virus and Cereal yellow dwarf virus (BYDV, CYDV: Luteoviridae) and Cocksfoot mottle virus (CoMV, Sobemovirus) are widespread throughout New Zealand. CoMV, previously considered to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Similarly, detection of Cocksfoot mottle virus (CfMV) in New Zealand is most probably of foreign origin as it has no beetle vector there [ 7 ] and its host plant cocksfoot has been introduced [ 8 ]. During recent decades, CfMV has colonized new native host species in New Zealand [ 9 ].…”
Section: Geographical Distribution Host Range Transmissionmentioning
confidence: 99%
“…Similarly, detection of Cocksfoot mottle virus (CfMV) in New Zealand is most probably of foreign origin as it has no beetle vector there [ 7 ] and its host plant cocksfoot has been introduced [ 8 ]. During recent decades, CfMV has colonized new native host species in New Zealand [ 9 ].…”
Section: Geographical Distribution Host Range Transmissionmentioning
confidence: 99%
“…Accordingly, relative quantification of the WDV titre in inoculated wheat and ryegrass plants evidently confirmed that the WDV titre is much lower in inoculated grass compared to infected cereal. A low titre of virus inoculum in grasses compared to cereals has been reported previously Accepted Article in the case of BYDV-PAV (Delmiglio et al, 2010). However, the transmission experiments show that even with a low virus titre, grass may still play a role in virus dissemination.…”
Section: Discussionmentioning
confidence: 63%
“…; Delmiglio et al . ), suggesting that communities that include P. pratensis and P. dilatatum will support greater virus prevalence. This effect could be magnified if the presence of these species increases virus transmission to other host species (Power & Mitchell ).…”
Section: Discussionmentioning
confidence: 99%
“…Such differences in infection prevalence among host species could be a result of species-specific characteristics that determine a host's ability to support vector populations, transmit infection to new hosts and/or ability to become infected (LoGiudice et al 2003;Borer et al 2007;Cronin et al 2010). These differences among host species can lead to effects of community composition on virus prevalence Delmiglio et al 2010), suggesting that communities that include P. pratensis and P. dilatatum will support greater virus prevalence. This effect could be magnified if the presence of these species increases virus transmission to other host species (Power & Mitchell 2004).…”
Section: Discussionmentioning
confidence: 99%